Collaboration and Its Distortion in Managing Migas’ CSR Programs: A Case Study on the CSEL’s Community Empowerment Program in the Salas Village, Bula Sub-District, Eastern Part Seram Regency, Maluku Province, Indonesia - Josep Antonius Ufi; Zainal Abidin Rengifurwarin; Jusuf Madubun (GoAcademica Research & Publishing, 2020)
This study aims to analyse the collaboration form of, and critically discuss the determinant factors of collaboration those are more significantly distorted, in the governance of CSEL’s CSR program on agriculture-based economic empowerment for communities in the Salas village of Bula Sub-District, Eastern Part of Seram Regency in Maluku Indonesia. The collaboration form, the determinant factors of collaboration and their distortion as the main focuses were employed in a qualitative case study. Primary data was collected by using an in-depth interview and Focus Group Discussion. There are 9 key informants. Secondary data was collected by using documentary study on relevant documents (CSR rule & regulation, CSR Reports, etc.). The CSEL’s collaborative CSR program was a type of formal collaboration that was significantly distorted. The stakeholder, communication and also collaboration resources were among the determinant factors which were significantly distorted in the governance of the CSEL’s collaborative CSR program, and therefore it failed for empowering the economy of the host community in the Salas Village. The findings of this study are useful to understand the specific formal collaborative management of CSR in Indonesian oil and gas sectors which were distorted in the CSEL’s collaborative CSR program case; particularly, these findings show the challenges the oil & gas sectors face in managing their collaborative CSR programs by improving the determinant factors of collaboration. This study adapts not only the concept of collaboration form, but also the well-known determinant factors of collaboration into a unique and specific case of CSEL’s formalized collaborative CSR program within the Indonesian oil & gas sectors context that was significantly distorted in practice if compared to other CSR programs of CSEL and others.